Income Analysis of Broiler Chicken Farmers Between Partnership and Independent Farming Systems in Tapian Dolok Subdistrict, Simalungun Regency - Ayu Dewi Annysa; Saidun Hutasuhut (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze and compare the income of broiler chicken farmers operating under partnership and independent business models in Tapian Dolok District, Simalungun Regency. The location was selected because Tapian Dolok is one of the broiler chicken production centers in Simalungun with a significant livestock population. The study employs a quantitative method with a descriptive comparative approach. The population consists of all broiler chicken farmers in Tapian Dolok District, and samples were selected using purposive sampling. Data analysis was conducted through cost analysis, revenue analysis, income analysis, R/C ratio analysis, and difference testing (independent sample t-test) to compare income between the two business models. This research is expected to provide comprehensive information regarding income levels, business efficiency, and the economic feasibility of each broiler farming model. The results indicate that the income per kilogram for independent farmers is IDR 25,000, while for partnership farmers it is IDR 18,000. In one business cycle, the average income received by independent farmers is IDR 88,995,189 and by partnership farmers is IDR 12,306,000. Comparative analysis shows a significant difference (P<0.05) in business income, with the independent model being more profitable due to higher income per bird than the partnership model